Enhancing Resilience of Low Income Workers in Brazil : Financial Instruments and Innovations - World Bank (World Bank, Washington, DC, 2021)
While the Brazilian social protection system provides instruments to reduce the risk of destitution from old age and disability with broad coverage, protection against labor income shocks in Brazil remains segmented and largely depends on labor status and household composition. In 2019, nearly one-third of households in Brazil lived below the Cadastro Único poverty line but many of them were above the eligibility threshold of Bolsa Família (BF). This note seeks to inform the design of a financial product and complementary actions that the government of Brazil could adopt to strengthen resilience of families in BF and Cadastro Único, particularly those working in the informal economy.